How Do Digital Readiness and Economic Growth Compare Across Income Groups? - Wiwiek Rindayati; Siti Aisyah; Gerhana Gerhana; Zhena Nofhatiaz Zahra (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study provides new empirical evidence on the global impact of digital readiness on economic growth by comparing high-, middle-, and low-income countries. Unlike previous studies focusing on single countries or regions, this research examines whether digital readiness contributes differently across income groups. Research Objectives: This study aims to explore the development of digital readiness and analyze its effect on economic growth across countries by income level. Research Methods: The study uses descriptive analysis and panel-data regression across 105 countries for 2019–2023. Digital readiness is measured by the Networked Readiness Index, comprising 46 indicators. PCA is applied to construct the index, and panel regression examines the relationship between digital readiness and economic growth across income groups. Empirical Results: Digital readiness significantly boosts economic growth across all income groups, with the strongest effect in high-income countries, a moderate effect in middle-income countries, and the weakest in low-income countries. Implications: The findings show that digital readiness has become a key driver of global economic growth, reflecting increasing access to and adoption of digital technologies across countries at different income levels. JEL Classification: O33, O40, F63 How to Cite:Rindayati, W., Aisyah, S., Gerhana, & Zahra, Z. N. (2026). How Do Digital Readiness and Economic Growth Compare Across Income Groups?. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 355-372. https://doi.org/10.15408/sjie.v15i2.51553.